The Influence of the Destination of IPO Capital Resources on the Shares Return - Yuri Bragancini Giacometti; Tabajara Pimenta Junior; Marcelo Augusto Ambrozini; Luiz Eduardo Gaio (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
In the IPO process, a prospectus is published that gathers relevant information for investors, including the funds raised destination. This study involved data from the period that covered two important crises for the Brazilian market – Subprime, in 2008, and President Impeachment, in 2016 – that preceded the actual Covid19 Crisis. From a sample of 103 IPOs that occurred between 2006 and 2015, historical series of stock quotes from 2006 to 2017, and using the event study procedure, we verified whether there were differences between the cumulative abnormal returns in the period after the IPO, of two groups of shares. One group was composed of companies that disclosed that the funds raised in the IPO would be used for direct investments (production, technologies, acquisitions, etc.), and the other group was composed of companies that announced that the resources would be applied in other destinations (indebtedness, working capital, credit to clients, etc.). We also seek to explain the behavior of returns accumulated abnormal returns, considering multiple linear regressions based on seven independent variables. The results showed that the announcement of direct investments with the funds raised in the IPO can generate positive abnormal returns in the very short term and showed signs of a relationship between the investment information and the behavior of the abnormal returns accumulated over one year after the IPO.